Analisis Metode Pembelajaran Bahasa Arab dalam Penerapan Kurikulum Berbasis Cinta (KBC) - Rahmadani, Mely; Setiyawan, Agung (Lembaga Yasin AlSys, 2026)
Although the integration of love values in Arabic language learning has received attention in various studies on Islamic education reform, research that specifically discusses the implementation of the Love-Based Curriculum (KBC) in Arabic language learning in pesantren-based madrasahs remains limited. This study aims to analyze the Arabic language learning methods applied at MA Mu’allimat Nahdlatul Wathan Diniyah Islamiyah Pancor within the KBC framework. This study employed a qualitative approach with a descriptive case study design, involving one Arabic language teacher and Grade XI Religious Studies students selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, field notes, and document analysis and were then analyzed using the Miles and Huberman interactive model. The results showed that the teacher applied a combination of audiolingual, question-and-answer, halaqoh, and talaqqi methods that were effective in overcoming students’ initial barriers, particularly shyness and low learning motivation. Students’ emotional aspects received special attention through the provision of appreciation, deep talk, and individual mentoring. The conclusion of this study affirms that the integration of KBC in Arabic language learning can create a supportive affective climate and encourage positive changes in students’ attitudes. These findings provide a theoretical contribution to the development of humanistic pedagogy in Islamic education and practical implications for madrasah teachers in designing love-based Arabic language learning. This study also opens opportunities for further research on the long-term impact of KBC on students’ character and Arabic language competence.